Advanced glycation end products modulate amyloidogenic APP processing and tau phosphorylation: a mechanistic link between glycation and the development of alzheimer's disease - Batkulwar, Kedar; Godbole, Rashmi; Banarjee, Reema; Kassaar, Omar; Williams, Robert J.; Kulkarni, Mahesh J. (ACS Chemical Neuroscience, 2018)
Advanced glycation end products (AGEs) are implicated in the pathology of Alzheimer's disease (AD), as they induce neurodegeneration following interaction with the receptor for AGE (RAGE). This study aimed to establish a mechanistic link between AGE-RAGE signaling and AD pathology. AGE-induced changes in the neuro2a proteome were monitored by SWATH-MS. Western blotting and cell-based reporter assays were used to investigate AGE-RAGE regulated APP processing and tau phosphorylation in primary cortical neurons. Selected protein expression was validated in brain samples affected by AD. The AGE-RAGE axis altered proteome included increased expression of cathepsin B and asparagine endopeptidase (AEP), which mediated an increase in A beta(1-)(42) formation and tau phosphorylation, respectively. Elevated cathepsin B, AEP, RAGE, and pTau levels were found in human AD brain, coincident with enhanced AGEs. This study demonstrates that the AGE-RAGE axis regulates A beta(1-)(42) formation and tau phosphorylation via increased cathepsin B and AEP, providing a new molecular link between AGEs and AD pathology.